Transcriptome Analyses of Chicken Primary Macrophages Infected With Attenuated Salmonella Typhimurium Mutants - Bhowmik, Bijit K.; Kumar, Arvind; Gangaiah, Dharanesh (Frontiers in Microbiology, 2022)
Salmonella enterica is one of the most common foodborne illnesses in the United States and worldwide, with nearly one-third of the cases attributed to contaminated eggs and poultry products. Vaccination has proven to be an effective strategy to reduce Salmonella load in poultry. The Salmonella Typhimurium Δcrp-cya (MeganVac1) strain is the most commonly used vaccine in the United States; however, the mechanisms of virulence attenuation and host response to this vaccine strain are poorly understood. Here, we profiled the invasion and intracellular survival phenotypes of Δcrp-cya and its derivatives (lacking key genes required for intra-macrophage survival) in HD11 macrophages and the transcriptome response in primary chicken macrophages using RNA-seq. Compared to the parent strain UK1, all the mutant strains were highly defective in metabolizing carbon sources related to the TCA cycle and had greater doubling times in macrophage-simulating conditions. Compared to UK1, the majority of the mutants were attenuated for invasion and intra-macrophage survival. Compared to Δcrp-cya, while derivatives lacking phoPQ, ompR-envZ, feoABC and sifA were highly attenuated for invasion and intracellular survival within macrophages, derivatives lacking ssrAB, SPI13, SPI2, mgtRBC, sitABCD, sopF, sseJ and sspH2 showed increased ability to invade and survive within macrophages. Transcriptome analyses of macrophages infected with UK1, Δcrp-cya and its derivatives lacking phoPQ, sifA and sopF demonstrated that, compared to uninfected macrophages, 138, 148, 153, 155 and 142 genes were differentially expressed in these strains, respectively. Similar changes in gene expression were observed in macrophages infected with these strains; the upregulated genes belonged to innate immune response and host defense and the downregulated genes belonged to various metabolic pathways. Together, these data provide novel insights on the relative phenotypes and early response of macrophages to the vaccine strain and its derivatives. The Δcrp-cya derivatives could facilitate development of next-generation vaccines with improved safety.